Contamination status and genetic characteristics of Clostridium perfringens in food in Liaoning Province - GENG Yingzhi; YU Miao; ZHANG Mingyan; ZHANG Meimei (Zhongguo shipin weisheng zazhi, 2022)
ObjectiveTo understand the contamination status, serotype and toxin genes characteristics of Clostridium perfringens (C. perfringens) in food samples in Liaoning Province.MethodsA total of 260 samples of raw meat and frozen surimi products were collected from 6 cities in Liaoning Province. The samples were tested for C. perfringens according to the national food safety standard GB 4789.13—2012. At the same time, the C. perfringens strains were identified by biochemical and fluorescent quantitative PCR method. Genotyping of toxin gene was detected by PCR method, and phylogenetic tree analysis was carried out for 16S rRNA gene sequence.ResultsA total of 15 C. perfringens strains were detected and the total detection rate was 5.8% in 260 food samples. The highest detection rate was 29% (9/31) in raw mutton. The result of toxin test showed that all strains detected α toxin. The detection rate of type A strains (α toxin) was 66.7%(10/15). The detection rate of type C strains (α toxin and β toxin) was 33.3%(5/15). There were 6 strains detected β2 toxin, including 4 strains of type A and 2 strains of type C. The detection rate of enterotoxin CPE was 6.7% (1/15). The 16S rRNA analysis showed that the genetic relationship of the strains carrying the same toxin gene was close.ConclusionC. perfringens strains were detected in raw animal meat and frozen surimi products in Liaoning Province, and the pollution of raw animal meat was serious. Moreover, there was a high risk of food poisoning mainly posed by type A and type C strains. Therefore, monitoring, prevention and control should be strengthened.